Significance assessment of the main risk factors of landing accidents based on the results of the survey of civil aviation pilots - V. V. Strelkov (Научный вестник МГТУ ГА, 2024)
To study the problem of rough landings and aircraft runway excursions, a 22-item questionnaire, related to the subject under consideration, was drawn up for pilots. The questionnaire mainly focused on aircraft veering off. The range of issues covered different aspects of the problem, including: pilots' perception and a comparative evaluation of various risk factors; personal experience of landings with prerequisites for a runway excursion; decision-making for the go-around procedure; attitude to the airline policy regarding the landing quality assessment; reliability of information reported to the crew about weather and runway conditions; quality of simulator training for flights in terms of crosswind and slippery runways; modern aircraft systems to prevent a runway excursion, etc. More than 50 civil aviation pilots of different age, experience, including aircraft captains and co-pilots were interviewed. The survey was conducted remotely and anonymously. The processing of the questionnaires included a detailed analysis of the answers to each question. If a question was not answered or if there was some reasonable doubt as to its correctness, the questionnaire was excluded from consideration. The results of questionnaire processing for the entire group and for individual categories (young/experienced, captains/co-pilots, turboprop/turbojet aircraft) were presented and analyzed in this paper.